Analysis of Risk Factors for Necrotizing Enterocolitis (NEC) in Newborns: A Systematic Literature Review - Putra, Reza Agustiantwo (Phlox Institute: Indonesian Medical Research Organization, 2024)
Necrotizing enterocolitis (NEC) is a serious condition in newborns involving inflammation and intestinal necrosis. A number of risk factors have been identified, which complexly interact and contribute to the development of this condition. An in-depth understanding of these risk factors has major implications for the prevention, diagnosis and management of NEC in newborns. Babies born prematurely, especially before 32 weeks' gestation, have a higher risk of developing NEC. Low birth weight, regardless of prematurity status, remains a significant independent risk factor. Imbalances in blood circulation, especially in the intestines, can increase the risk of NEC. Hypotension and other medical conditions that affect blood flow to the intestines can be potential triggers. Infection and inflammation, both systemic and local, play a central role in the development of NEC. Bacterial contamination in the digestive tract can trigger an inflammatory response that contributes to the pathophysiological process of NEC. Formula feeding, especially in premature infants, is associated with an increased risk of NEC. The importance of providing exclusive breastfeeding and introducing foods slowly to protect the newborn's intestinal health. Excessive use of antibiotics or without clear indications can change the balance of intestinal microflora and increase the risk of NEC. The importance of judicious selection and use of antibiotics to minimize negative impacts on gut health.